2019
DOI: 10.5797/jnet.cr.2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Transverse-sigmoid Sinus Dural Arteriovenous Fistula Treated by Transarterial and Transvenous Embolization via the Balloon Microcatheter with Overinflated Balloon Protection of the Torcula

Abstract: Objective:The objectives of treating dural arteriovenous fistula (dAVF) are to achieve complete occlusion of the arteriovenous (AV) shunt and restoration of anterograde venous flow. We report a patient with complex dAVF who was managed by double overinflated balloon protection of the torcula and percutaneous transluminal angioplasty (PTA) for the occluded venous sinus. Case Presentation:A 62-year-old woman was admitted with gradually worsening nausea and vomiting, as well as progressive memory disturbance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…If one balloon is unable to create a large enough wall, placing the two in parallel is possible. The strategy was different from ours, and the balloon was not used to assist the approach; however, Yabuzaki et al reported a case of DAVF treated using two balloons in the sinus [11]. The duration of complete occlusion of the sinus, including SSS, is unknown, but even with incomplete occlusion as in our case, the balloon can function well as a wall.…”
Section: Discussionmentioning
confidence: 70%
“…If one balloon is unable to create a large enough wall, placing the two in parallel is possible. The strategy was different from ours, and the balloon was not used to assist the approach; however, Yabuzaki et al reported a case of DAVF treated using two balloons in the sinus [11]. The duration of complete occlusion of the sinus, including SSS, is unknown, but even with incomplete occlusion as in our case, the balloon can function well as a wall.…”
Section: Discussionmentioning
confidence: 70%
“…Table 1 shows a summary of these cases. [4][5][6][7][8] This is the first case reporting in detail about dilatation of the occluded sinus associated with DAVF over time after balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sinus diameter exceeds 10 mm in some cases, in which parallel arrangement of several balloons may be adopted. 4) Using balloons available in Japan, it is difficult to obliterate the normal sinus using those for standard aneurysmal neck remodeling due to their inflated diameters. Furthermore, PTA balloons for the carotid artery or peripheral blood vessels were also initially used after the introduction of this procedure (2008).…”
Section: Characteristics and Usage Of Balloon Cathetersmentioning
confidence: 99%
“…In areas with a vascular diameter of >14 mm, such as the sinus confluence, it is possible to obliterate the orifice of a shunt to the sinus by inserting several balloons in parallel. 4) The usage of the Shoryu is summarized below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation